Determination of high quality of Echinaceae purpurae herba grown in Uzbekistan and the prospect of creating immunomodulatory medicinal products on its base - Zuparova, Zulfia A. (International Journal of Psychosocial Rehabilitation, 2020)
As it known, immunostimulatory medicines present synthetic, biotechnological and natural substances which are able to effect on different links of the immune system and change the strength, nature and direction of immune responses. [2]. Medicinal plants and medicines made of them are valuable raw materials for producing of medicines in the treatment of various diseases related to disruption of functional activity of the immune system. Medications made of Echinaceae purpurae herba are the most widely used plant-based medicines applied in various forms of immunodeficiency. The therapeutic properties of Echinaceae purpurae are due to the unique chemical composition of all parts of the herb. Rich vitamin-mineral composition of Echinacea purpurae specifies its immunomodulatory, anti-inflammatory, antiallergenic, antimicrobial effect. Especially polysaccharides of Echinaceae purpurae have expressed pharmacological activity. The aim andtask of the present research is to find out and analyze the chemical-biological composition of Echinaceae purpurae. Besides, to implement into the medical practice domestic highly effective, low-toxic medicines of immunomodulatory and immunostimulatory effect on the base of medicinal plant raw material of Echinaceae purpurae herba. Objective of the studyis determination of high quality of Echinaceae purpurae herba grown in Uzbekistan, and the analysis of the immunomodulatory medicinal products assortment. Materials and Methods of the study.In the present work such methods and deviceswere applied, as the method of chromato-mass-spectrometry analysis (a chromato-mass spectrometer of “Agilent Technology” company GC/MS AT 5973N), IR-spectrum(for obtained polysaccharides), ICP-MS (Inductively Coupled Plasma Mass Spectrometer) AT 7500a (for determination of heavy metal micro-composition), the method of GF XI of the issue 2 and to change № 2, dated 12.10.2005 of category 4B (for determination of microbiological purity). In the process of analysis, the State Registers of medicines and medical products of the Republic of Uzbekistan for 2019, № 23 were used as the materials. For determination ofhigh quality of Echinaceae purpurae herba raw material, such indicators as moisture content, ash content, protein, fatty acids, essential amino acids and microelements have been researched, as well as the assortment composition of immunomodulatorymedicinal products was studied, in order to create perspective medicinal products from Echinaceae purpurae herbagrown in Uzbekistan.